Process Evolution based on Transformation of Algebraic High-Level Nets with Applications to Communication Platforms - Gabriel, Karsten (Electronic Communications of the EASST, 2012)
Algebraic High-Level (AHL) nets are a well-known modelling technique based on Petri nets with algebraic data types, which allows to model the communication structure and the data ﬂow within one modelling framework. Transformations of AHL-nets – inspired by the theory of graph transformations – allow in addition to modify the communication structure. Moreover, high-level processes of AHL-nets capture the concurrent semantics of AHL-nets in an adequate way. In this paper we show how to model the evolution of communication platforms and scenarios based on transformations of algebraic high-level nets and processes. All constructions and results are illustrated by a running example showing the evolution of Apache Wave platforms and scenarios. The evolution of platforms is modelled by the transformation of AHL-nets and that of scenarios by the transformation of AHL-net processes. Our main result is a construction for the evolution of AHL-processes based on the evolution of the corresponding AHL-net. This result can be used to transform scenarios in a communication platform according to the evolution of possibly multiple actions of the platform.